"A Place of Pain and Gain": Exploring the Dynamics of Resistance in the Creation of Sengwe Tshipise Wilderness Corridor, Southeast Zimbabwe. Issue 8 (3rd August 2017) - Chirozva, Chaka; Black, Rosemary; Higgins, Vaughan
ABSTRACT: This article examines the relationship between place attachment and resistance during participatory planning of the Sengwe Tshipise Wilderness Corridor, located in southeast Zimbabwe, a region that falls within the Great Limpopo Transfrontier Conservation Area. Field research was conducted from July to December 2013 using 69 semistructured interviews, seven focus-group discussions, and analysis of secondary data. By following the dominant narratives articulated by villagers affected by this Corridor, we illustrate the multiple ways in which place attachment becomes part of everyday politics of resistance. Results show that a strong place-based identity is at the center of narratives deployed by villagers displaced by war, conservation, and veterinary fencing restrictions. Through deploying this place-based identity, communities collectively influenced both the spatial extent of the corridor and institutional governance arrangements. This article contributes to debates on the role of community agency in the implementation of transfrontier conservation areas.